Pengaruh Ketinggian Genangan dan Jenis Pupuk Teh Kompos terhadap Pertumbuhan dan Hasil Pakcoy (Brasicca rapa L.) Secara Hidroponik - Raharjo, Krisantus Tri Pambudi; Kapitan, Origenes Boy; Nahak, Pius Robertus (Savana Cendana, 2023)
Pakcoy (Brassica rapa L.) is a type of vegetable plant that belongs to the Brassicaceae family. The pakcoy plant originates from China and has been widely cultivated after the 5th century in China. Besides being a natural fertilizer, compost tea can also function as a natural pesticide, because it can restore soil fertility naturally and increase plant resistance to pests and diseases. The application of compost tea in addition to increasing the nutrient content of the soil can also increase the population of beneficial microorganisms to increase soil fertility. Application on leaves, can suppress the development of pathogens that cause leaf diseases. Research has been carried out in the faculty’s garden. Timor University Agriculture, Sasi Village, Kefamenanu City District, TTU Regency. The time needed to complete the research from April to May 2018. The materials to be used in this study are as follows; pakcoy seeds, husk charcoal, dulang, AB MIX nutrition, 8.5 cm diameter bucket, guano fertilizer, talirafia, the tools to be used in the research are as follows; machete, crowbar, scissors, cutter, hammer, nails, saw, ruler, book/pen. This study will use a factorial completely randomized design (CRD) (3 x 3) repeated 3 times. The first factor is the height of the puddle (A) which consists of 3 levels, namely: 3 cm (A1) Gamal tea compost, 6 cm (A2) Guano tea and 9 cm. The second factor is the type of organic liquid fertilizer, namely: AB Mix (J1), guano (J2), and Gamal Leaf Compost (J3). The treatment combinations were A1J1, A2J1, A3J1, A1J2, A2J2, A3J3, A1J3, A2J3, and A3J3. The results showed that there was an interaction of the effect of inundation height and the type of compost tea fertilizer on the parameters of leaf number and leaf area, but there was no interaction on crop yields. The data showed the highest moisture content and neutral soil pH, Husk Hydrogen Potential, highest growth, plant height, number of leaves, fresh weight of the heaviest plant, total fresh weight, fresh weight of husk, obtained from a water height of 3 cm and the addition of guano compost tea.